The Wall Street Rule and its Impact on Board Monitoring - Chen, B.; Duong, Lien; Truong, T. (2018)
The “Wall Street Rule” (WSR), a form of monitoring by institutional investors, has been viewed as a “cut-and-run” strategy adopted to express dissatisfaction with a company’s management. In this study, we show that WSR, far from being a passive protest, is in fact a potent weapon to improve corporate governance. We present empirical evidence that WSR is positively associated with board monitoring when the firm is endowed with an outsider-dominated board. This suggests that WSR improves stock price informativeness, providing the board with an additional source of information so that it may monitor the company more effectively.